A study on the factors that involved in improving quality of services in Jabatan Tenaga Kerja Batu Pahat / Fairuz Izzati Othman - Othman, Fairuz Izzati (Faculty of Business and Management, 2010)
The study is focuses on the quality of service culture in Jabatan Tenaga Kerja Batu Pahat. There have three objective of this research study. Firstly is to measure the relationship of quality of services in term of technology, management commitment, and trained staff in JTKBP. Secondly is to identify the most influencing factor to improve quality of services in JTKBP. And lastly to suggest an appropriate recommendation that is believed to improve the quality of services in JTKBP. This study concentrates on 3 variables of quality of services in JTKBP. The dependent variable is quality of services at the JTKBP. For the independent variables there are technology, management commitment, and trained staffs. Data collected was analyzed by using the Statistical Package for Social Science (SPSS). Primary data was collected using a questionnaire. Sampling techniques has been used in this study was census, all the staffs have been chosen as respondent. The results proved that there was relationship between quality of services with technology and trained staffs. Beside that, in the chapter four will explain the finding analysis and interpretation in this study. This chapter comprises the frequency analysis, regression analysis, and correlation analysis. The finding reveals that trained staffs were the most influence factor in the JTKBP, Johor